PENGARUH KOMPETENSI, PENGALAMAN KERJA DAN INSENTIF TERHADAP PRODUKTIVITAS KERJA KARYAWAN PERKEBUNAN PT. EKADURA INDONESIA KABUPATEN ROKAN HULU - Desi Permata Sari; Machasin Machasin; Arwinence Pramadewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to determine the effect of competence, work experience andincentives on work productivity of plantation employees of PT. EkaduraIndonesia, Rokan Hulu Regency. The population in this study includes employeesat PT. Ekadura Indonesia, totaling 95 people. Primary data was collected byusing a questionnaire as an instrument to prove the results of the study, to test thehypothesis in this study using Multiple Linear Regression Analysis with the help ofthe SPSS program. The sampling technique that has been selected is saturatedsampling, totaling 95 people. The results in the study indicate that: 1)Competence affects the work productivity of plantation employees of PT. EkaduraIndonesia Rokan Hulu Regency 2) Work experience affects the work productivityof plantation employees of PT. Ekadura Indonesia Rokan Hulu Regency 3)Incentives affect the work productivity of PT. Ekadura Indonesia Rokan HuluRegency 4) Competence, work experience and incentives affect the workproductivity of plantation employees of PT. Ekadura Indonesia Rokan HuluRegencyKeywords: Competence, Work Experience, Incentives, Work Productivity